Hubungan Antara Tingkat Pendidikan dan Pengetahuan Orangtua dengan Kualitas Hidup Anak Talasemia Mayor di RSUD Dr. M. Yunus Bengkulu - Karissa Faraski; Wasis Rohima; Sylvia Rianissa Putri (Syntax Idea, 1992)
One of the problem in thalassemia children is poor quality of life. It is assessed through 4 functions, namely physical, emotional, social, and school functions. Many factors affect the quality of life in thalassemia patients. This study is aimed to know the relationship between educational level and knowledge of parents, with the quality of life in thalassemia children. A cross-sectional study with 54 subjects with thalassemia and 54 pairs of parents. Subjects who met the inclusion criteria and did not meet the exclusion criteria were taken by the consecutive sampling method. Data collection technique was done by conducting interviews based on characteristic data questionnaires, parental knowledge questionnaires, and quality of life questionnaires using PedsQL 4.0 Core Scales. We analised the data by Spearman correlation test and Pearson correlation test. Maternal’s educational level has a significant correlation to the quality of life in children with thalassemia with moderate correlation strength on spearman test (r = 0,410; p = 0,002). Father’s educational level has a significant correlation to the quality of life in the children with thalassemia with a weak correlation strength (r = 0.359; p = 0.008) on the spearman test. Maternal’s level of knowledge have significant correlation to the quality of life in children with thalassemia with medium correlation strength (r = 0,404; p = 0,002) on spearman test. Father’s level of knowledge have significant correlation to quality of life in children with thalassemia with weak correlation strength (r = 0,335; p = 0,013) on the spearman test. Multivariate test found that most factors affecting the quality of life of children with thalassemia is the level of knowledge of mothers with p = 0.014 and OR = 1.179. There is a significant correlation between the level of education and knowledge of parents on the quality of life of major thalassemia children.